Carbon emission analysis and improvement of electrical machines - Zhang, Xuebei (2025)
The urgent need to restrain carbon (CO2) emissions in response to climate change has led the electrical machinery industry to prioritise improved performance and efficiency. Previous research has predominantly focused on electromagnetic design and thermal management to increase machine efficiency for reduced CO2 emissions. However, methodologies for calculating the embedded CO2 emissions associated with the materials and manufacturing technologies of electrical machine components are rarely reported. With the UK aiming to achieve net-zero emissions by 2050, all aspects of embedded carbon within the machine need to be reviewed. To establish a truly sustainable framework for the assessment of embedded CO2, this thesis addresses the gap in the literature by focusing on the carbon emissions from the early design and production stages. In particular, the carbon emissions associated with raw materials of a commercial benchmark wound field synchronous machine (WFSM) represent a significant proportion, up to 89% of the total emissions during the manufacturing phase of electrical machines. Therefore, a novel material selection guideline is established within this thesis to reduce carbon emissions during the primary production of the main components of electrical machines. It enables a comprehensive approach integrating mechanical, thermal, electromagnetic, and environmental impact considerations at early production stages. This holistic perspective is useful to advance the design of electrical machines to support environmental protection and sustainable energy practices. Pursuing alternative materials and efficient manufacturing processes is emerging as a key strategy for advancing the overall sustainability of electrical machines. Based on the aforesaid material selection guideline, three different types of commercial electrical machines, each with a similar power rating, are evaluated and compared: one WFSM, one induction machine (IM) and two permanent magnet machines (PM#1 and PM#2). An understanding of the environmental impact of these machines is achieved by assessing both the embedded carbon in the constituent materials of the machines and the operational emissions. The embedded carbon emission analysis of raw material demonstrates that WFSM is the most carbon-efficient, whereas the PM machines have the highest material emissions due to their dependence on high-emission magnets. The analysis also shows that operational emissions can outweigh material emissions for all machine types. This highlights the critical role of machine efficiency in determining the overall carbon footprint, where PM machines have led to lower total emissions due to their superior efficiencies. Based on the material selection guide, the benchmark WFSM machine is further investigated and improved across multiple materials and design parameters from an embedded CO2 emissions standpoint. Factors such as reduced carbon footprint and component mass are considered without compromising current electromagnetic performance. The thesis study results show a significant opportunity for improvement in the embedded emissions of CO2 and component mass by 35.37% and 34.95% respectively, on the benchmark machine components achieved by applying alternative materials and improved design insights established in this thesis. The results demonstrate the significant environmental benefits that can be achieved by using alternative materials in the critical components of electrical machines. Overall, this thesis presents a comprehensive analysis of carbon emissions of electrical machines, aimed at providing a holistic understanding of the environmental impacts associated with the primary production stages of electrical machines, thereby supporting informed decision-making for carbon reduction and promoting sustainable practices across various sectors.